Strengths and Resilience Among Central American Parents Seeking Asylum in the United States. (June 2023) - Morales, Frances R.; Hawkins, Kathleen; Gonzalez, Danielle; Garcia, Alexander; Patel, Sita G.; Mercado, Alfonso
This study examined the experiences of immigrant parents seeking asylum in the United States after recently fleeing the Northern Triangle region of Central America, attending both to the traumatic events and the strengths that mitigate this experience. The study employs a convergent parallel mixed-methods design to describe the experiences of 51 parents after being processed by U.S. immigration officials for seeking asylum. Quantitative analyses measured trauma exposure and psychological distress and posttraumatic stress symptoms, as well as religiosity, dispositional optimism, and perceived quality of life. Qualitative analyses examined migratory experiences more deeply. Quantitative findings suggest that participants displayed high levels of resilience as evidenced by the low endorsement of mental health symptoms associated with trauma despite high violence and trauma exposure. Qualitative analyses revealed two themes underscoring strengths that mitigated the compounded trauma experienced by participants, including: (a) protective factors, and (b) plans for the future. In addition, several subthemes emerged within each of these broader themes. Qualitative findings highlight that asylum seekers come to the United States for the sake of their families, especially their children. Participants shared their desire to ensure the safety of their family and children and their hope of being better able to take care of them. These desires and hopes common among participants in our study not only motivated them to leave their home countries but also helped them to press forward in their journeys. Study results show that religiosity, hope, and optimism also played important roles in sustaining these immigrant parents during their journeys.